Monitoring in non-traumatic coma. Part II: Electroencephalography. Issue 8 (August 1988) - Tasker, R C; Boyd, S; Harden, A; Matthew, D J
Abstract : Forty eight comatose children had electroencephalograms (EEG) recorded during the acute phase of their illnesses. These were classified according to a simple grading system and the findings correlated with the presence of seizures, deep coma, minimum cerebral perfusion pressure, and eventual neurological outcome. Serial EEGs proved important, particularly when slow activity was seen initially. None of the 20 patients who showed low amplitude EEG activity or electrocerebral silence at any stage of the acute illness did well. Discharges were seen in only 13 of the 29 patients with seizures and their presence did not correlate with outcome except in five patients with a distinctive pattern of discharges, none of whom had a good outcome. EEG findings associated with poor outcome did not always correlate with the clinical assessment of deep coma, emphasising the difficulties of neurological evaluation in these patients. Five of the patients with cerebral perfusion pressures greater than 42 mm Hg had a poor outcome that was predicted by serial EEGs. In nine patients with a minimum cerebral perfusion pressure in the borderline range 38-42 mm Hg the EEG was useful as an indication of the outcome. The EEG reflects changes in cerebral function which may be due to multifactorial or repeated insults. An EEG is therefore important in both the initial assessment and as an indicator of the neurological outcome, particularly in those patients in whom the cerebral perfusion pressure has apparently been adequate or within the borderline range.